Identification of an Effector Specificity Subregion within the Aromatic-Responsive Regulators DmpR and XylR by DNA Shuffling - Skärfstad, Eleonore (American Society for Microbiology, 2000)
The Pseudomonas derived ς(54)-dependent regulators DmpR and XylR control the expression of genes involved in catabolism of aromatic compounds. Binding to distinct, nonoverlapping groups of aromatic effectors controls the activities of these transcriptional activators. Previous work has derived a common mechanistic model for these two regulators in which effector binding by the N-terminal 210 residues (the A-domain) of the protein relieves repression of an intrinsic ATPase activity essential for its transcription-promoting property and allows productive interaction with the transcriptional apparatus. Here we dissect the A-domains of DmpR and XylR by DNA shuffling to identify the region(s) that mediates the differences in the effector specificity profiles. Analysis of in vivo transcription in response to multiple aromatic effectors and the in vitro phenol-binding abilities of regulator derivatives with hybrid DmpR/XylR A-domains reveals that residues 110 to 186 are key determinants that distinguish the effector profiles of DmpR and XylR. Moreover, the properties of some mosaic DmpR/XylR derivatives reveal that high-affinity aromatic effector binding can be completely uncoupled from the ability to promote transcription. Hence, novel aromatic binding properties will only be translated into functional transcriptional activation if effector binding also triggers release of interdomain repression.